Comparison of Physical Activity Among Private and Public Undergraduates Medical Students - Mansab Ashfaq, Waleed Tariq, M. Ahsan Ishfaq, Aliza Khan, Mahnoor Hassan, (Pakistan Journal of Medical & Health Sciences, 2022)
Medical students and other health care professionals have substantial knowledge of the benefits of regular physical activity. Furthermore, as they have an ethical obligation to prescribe suitable exercises, they can influence their patients’ attitude toward physical activity and can become role models for their patients. Study design is cross-sectional. The questionnaire of research was distributed among 200 private medical students and 200 public medical students from different medical. Non Probability Convenience Sampling Technique was adopted to select the study population. International Physical Activity Questionnaire (IPAQ) (10) was developed which consists of different questions about their routine physical activities. Data was recorded anonymously, and we respected the confidentiality of the respondents. In our basic study there were a total of 400 medical. The study subjects included 26 % males and 74 % females in private sector and 19 % males and 81 % females in public sector. 29.5 % population belonged to 1st professional year and 70.5 % senior years in private sector whereas in public sector 69.5 % population belonged to 1st professional years and 30.5 % in senior years. The mean age of students is 21.9. And results obtained were not significant statistically and there was a lack in physical activity of both sectors almost on a par. The corresponding comparison of knowledge, attitude and practices of medical students between private and public sectors suggests that adequate knowledge about physical activity is not sufficient. There were a large number of medical students of both sectors who, despite being aware of benefits of physical activity, did not meet the recommended level of physical activity the reason as to why the results obtained were not significant statistically. Keywords: medical,physical,undergraduates,activity